2022
DOI: 10.1002/bmc.5488
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination and pharmacokinetic study of six components in beagle dog plasma by UPLC–MS/MS after oral administration of Astragalus Membranaceus aqueous extract

Abstract: Astragalus Membranaceus (AM) is widely applied in Chinese herbal compound formulas for treating various kinds of diseases. However, relative pharmacokinetics data on AM in nonrodents is still lacking. Here, an UPLC-MS/MS method for determining the six main compounds of AM was developed. The chromatographic separation was carried out by a Waters Acquity UPLC HSS T3 column (100 Â 2.1 mm, 1.8 μm) with gradient elution of water-formic acid (99.98:0.02, v/v) and acetonitrile-formic acid (99.98:0.02, v/v) at a flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Some components in traditional Chinese medicine such as flavonoids, etc., present low oral bioavailability. However, different formulations could improve oral bioavailability [ 30 ]. Moreover, the compound CAM106 is poorly soluble in water, so the formulation particle size can be changed to improve bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Some components in traditional Chinese medicine such as flavonoids, etc., present low oral bioavailability. However, different formulations could improve oral bioavailability [ 30 ]. Moreover, the compound CAM106 is poorly soluble in water, so the formulation particle size can be changed to improve bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Huang Qi is a major medicinal herb widely used in TCM formulas, which has been proved to be effective against CHF [ 33 ]. Modern pharmacological research has shown that the major components in Huang Qi can protect myocardial cells, enhance myocardial contractility, regulate immunity, and improve circulation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absolute oral bioavailability of Astragaloside IV is only 7.4% and 2.2% in beagle dogs and rats, respectively ( Gu et al, 2004 ; Zhang et al, 2007 ). After oral administration of Astragalus aqueous extract (4 g/kg raw herb), the peak concentration (Cmax) and elimination half-life (t1/2) of Astragaloside IV is 7.99 ± 5.97 ng/ml and 5.09 ± 2.26 h in beagle dogs ( Yu et al, 2022 ). Intravenous administration has greater bioavailability than oral administration, about 50% of Astragaloside IV can be metabolized in vivo by intravenous administration in rats ( Du et al, 2005 ).…”
Section: Astragalus and Its Active Antifibrotic Componentsmentioning
confidence: 99%